Facile synthesis of ZnFe2O4 with inflorescence spicate architecture as anode materials for lithium-ion batteries with outstanding performance. (2nd March 2015) - Hou, Xianhua; Wang, Xinyu; Yao, Lingmin; Hu, Shejun; Wu, Yuping; Liu, Xiang
<x xml:space="preserve">Abstract</x> Inflorescence spicate ZnFe2O4 with outstanding electrochemical performance has been synthesized using a simple method based on precipitation.